Karakteristik Material Tanah Galodo Gunung Marapi terhadap Potensi Bencana - Riadi, Irvan; Hakam, Abdul; Andriani, Andriani (Universitas Batanghari Jambi, 2025)
Mount Marapi in West Sumatra is an active mountain with a history of disasters, including galodo or flash floods due to eruptions and high rainfall. The soil material carried by the galodo greatly influences the potential for disaster. This research analyzes the classification and characteristics of galodo soil material and its relationship with disaster potential, as well as determining mitigation efforts that can be carried out. This research method uses laboratory experiments. Soil samples were taken from 16 points at seven river locations, namely Batang Jambu, Batang Malanang, Batang Bangkahan, Batang Arau, Sungai Talang, and Batang Anai, with a distance of 50 meters between points. Samples were collected in the form of disturbed soil, which was then analyzed to determine its physical and mechanical properties. The results showed that the galodo soil material was classified as sand (SW), silty sand (SM), and clayey sand (SC). Its physical properties include a specific gravity of 2.65-2.67, a bulk density of 1.61-1.96 gr/cm3, and a plasticity index of 8.25-9.17%. Mechanically, the soil has a cohesion of 0.029–0.071 kg/cm2 and a deep shear angle of 26.57–37.77°. These characteristics indicate non-cohesive properties, so when saturated due to high rainfall, the pore water pressure increases and causes high-speed debris flow. The kinetic energy of these flows can damage riverbanks, settlements, and infrastructure. Mitigation measures include structural measures such as the construction of check dams, groundsills, and sabo dams, as well as non-structural measures such as early warning, disaster education, and limiting settlements on riverbanks.